2015
DOI: 10.1111/jch.12712
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hypertension Screening in Childhood Using Modified Blood Pressure to Height Ratio

Abstract: Blood pressure to height ratio (BPHR) has been suggested as a simple method for screening children with hypertension, but its discriminatory ability in young children is not as good as that in older children. Using data of 89,664 Chinese children aged 7 to 11 years, the authors assessed whether modified BPHR (BP:eHT13) was better than BPHR in identifying young children with hypertension. BP:eHT13 was estimated as BP/(height+7×(13−age in years)). Using Youden's index, the thresholds of systolic/diastolic BP:eHT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Previous studies that compared the efficacies of different BPHR indices on identification of HBP in children have produced discrepant results 13‐17 . The findings in our study are consistent with the study reported by Zhang et al 17 In their study, the authors compared the efficacy of MBPHR3 and MBPHR7 with BPHR3 in young American and Chinese children and found MBPHR3 had a better predictive performance in identifying HBP compared to BPHR and MBPHR7, but only in American children but not in Chinese children, in whom the MBPHR7 achieved better performance than BPHR and MBPHR3 17 …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Previous studies that compared the efficacies of different BPHR indices on identification of HBP in children have produced discrepant results 13‐17 . The findings in our study are consistent with the study reported by Zhang et al 17 In their study, the authors compared the efficacy of MBPHR3 and MBPHR7 with BPHR3 in young American and Chinese children and found MBPHR3 had a better predictive performance in identifying HBP compared to BPHR and MBPHR7, but only in American children but not in Chinese children, in whom the MBPHR7 achieved better performance than BPHR and MBPHR3 17 …”
Section: Discussionsupporting
confidence: 83%
“…In a study by Ma et al 14 on hundred Chinese children aged between 7 and 12 years, MBPHR3 showed an acceptable performance compared with MBPHR7 and BPHR.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The main advantage of these formulas is the simplicity of data needed to evaluate a child's BP status, including only office BP values and height. Although the initial blood‐pressure‐to‐height ratio was appealing in terms of ease to use, the newer modified blood‐pressure‐to‐height ratios [BP/(height (cm) + 7 (13‐age), and BP/(height + 3 (13‐age)] 7,8 may further compel the physician to familiarize and memorize more complex mathematical formulas. This could be a first limitation for their use in clinical practice beyond epidemiological studies, in which statistical formulas facilitate the calculation of the modified ratios.…”
mentioning
confidence: 99%